A study of neoplastic study of gastrointestinal tumors - Dr. Aarti Parmar; Dr. Mayur Jitu bhai Kokani; Dr. Manisha Patel (Tropical Journal of Pathology and Microbiology, 2018)
Background: Gastrointestinal tumors account for a large proportion of all neoplasms. The tumors of the Gastrointestinal tract pose a major problem in oncology and also are a major cause of apprehension in patient with the abdominal complaint in whom the fear of the cancer is the greatest. There is world wide variation in the distribution of these neoplasm, which appear largely due to exogenous factors rather than genetic.Objectives: to determine the relative frequency of various histopathologic types of tumors of eosophagus, stomach and intestines, and knowledge about their prognosis will aid the clinician in effective management of patient.Methodology: It was a prospective observational study carried after permission of the institutional ethics committee. All biopsies and resected specimens of GIT with neoplastic lesions were examined for gross lesions. All specimens studied under light microscopy and tumors were classified according to the WHO International classification of Tumors of the esophagus, stomach and intestines.Results: Gastrointestinal tumor distributed throughout all age group with maximum in 5th and 6th decade of life with male:female ratio was 1.67:1. Out of 18 cases of esophageal tumors, 16 were of squamous cell carcinoma, 1 case of adenosquamous carcinoma and 1 case of basaloidsquamous carcinoma. Majority of cases of gastric tumors occurred in pylorus followed closely by body of the stomach. Out of 18 cases of colorectal carcinoma, 12 cases were adenocarcinoma, 3 were mucinous adenocarcinoma, 2 cases of Signet ring cell carcinoma and 1 case of Malignant melanoma.Conclusion: Tumors of the gastrointestinal tract show a wide variation in the histological type making the histopathological examination a must in the diagnosis of these tumors. Early diagnosis and treatment is beneficial for better management and is imperative in providing better quality of life to the patient.